A simple and direct ionic chromatography method to monitor galactose oxidase activity. Issue 40 (13th September 2022) - Kaddouch, Eden; Cleveland, Maria E.; Navarro, David; Grisel, Sacha; Haon, Mireille; Brumer, Harry; Lafond, Mickaël; Berrin, Jean-Guy; Bissaro, Bastien
Abstract : Galactose oxidase (GalOx, EC.1.1.3.9) is one of the most extensively studied copper radical oxidases. Here, we show it can be monitored through the release of oxidized galactosylated products using a simple, direct and sensitive HPAEC-PAD method. Abstract : Galactose oxidase (GalOx, EC.1.1.3.9) is one of the most extensively studied copper radical oxidases (CROs). The reaction catalyzed by GalOx leads to the oxidation of the C-6 hydroxyl group of galactose and galactosides (including galactosylated polysaccharides and glycoproteins) to the corresponding aldehydes, coupled to the reduction of dioxygen to hydrogen peroxide. Despite more than 60 years of research including mechanistic studies, enzyme engineering and application development, GalOx activity remains primarily monitored by indirect measurement of the co-product hydrogen peroxide. Here, we describe a simple direct method to measure GalOx activity through the identification of galactosylated oxidized products using high-performance anion-exchange chromatography coupled to pulsed amperometric detection (HPAEC-PAD). Using galactose and lactose as representative substrates, we were able to separate and detect the C-6 oxidized products, which were confirmed by LC-MS and NMR analyses to exist in their hydrated (geminal-diol) forms. We show that the HPAEC-PAD method is superior to other methods in terms of sensitivity as we could detect down to 0.08 μM of Lac OX (eq. 30 μg L −1 ). We believe the method will prove useful for qualitative detection of galactose oxidase activity in biological samples or for quantitative purposes to analyze enzyme kinetics or to compare enzyme variants in directed evolution programs.